Factors affecting men’s support for the use of the contraceptive implant by their female intimate partners - Jonas, Kim (Contracept Reprod Med, 2020)
BACKGROUND: Family planning services have been available at no cost in the public health settings of South Africa since 1994, and now include the long-acting reversible contraceptives (LARCs) namely, the contraceptive implant and intra-uterine device (IUD). However, the uptake of LARCs has been declining in the recent years and little is known about the cause of the decline. In many relationships, men may influence their female intimate partner’s contraceptive choices. Thus, men’s involvement in reproductive health decisions and family programming may improve their support for contraceptive use, including the LARC use by their female intimate partners. This study investigated factors affecting men’s support for the use of contraceptive implant by their female intimate partners. METHODS: A quantitative, cross-sectional survey was conducted among adult men attending a public, primary health clinic in Cape Town, South Africa. Using a structured questionnaire, we measured men’s knowledge, awareness and support of, and attitudes towards use of the contraceptive implant by their female intimate partners. Data were analyzed using SPSS version 25. RESULTS: The sample included 65 men with a mean age of 31.2 years. Most (76.6%) believed that both men and women should be responsible for family planning. Support for general contraception use by their female intimate partners was prevalent at 80.0%, but only 33.9% reported that they would like their partners to use the implant in the future, while 35.6% were unsure and 30.5% did not support their partner’s use of the implant. Factors significantly associated with men’s support of their partner’s future use of the contraceptive implant included men’s reports that their partner wished to have another child in future, knowledge that the implant is safe for use by women who have not had children, knowledge that the implant can effectively prevent pregnancy for 3 years, and a positive attitude towards the implant’s long-lasting effectiveness. CONCLUSION: Improving men’s knowledge of, and attitudes toward the contraceptive implant might increase their support for their partner’s use of the implant, which in turn might promote uptake of the implant among women. The findings of our study suggest the importance of actively engaging men in reproductive health and family planning programs. SUPPLEMENTARY INFORMATION: The online version contains supplementary material available at 10.1186/s40834-020-00140-7.